1946
DOI: 10.1104/pp.21.2.237
|View full text |Cite
|
Sign up to set email alerts
|

Leafspot of Peanut Associated With Magnesium Deficiency

Abstract: It is generally recognized that the susceptibility and prevalence of manv plant diseases are associated with plant nutrition. The peanut plant is susceptible to leafspot infection which becomes economicallv important during the last half of its growth period when the crop is planted in the spring. The severity and rapid spread of infection in the field may not be due to the mere presence of the organism, which is ubiquitous, but to the susceptibility of plants suffering from improper niutrition in certain stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

1949
1949
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Magnesium deficiency as previously reported by BLEDSOE, et al, (2) (19) indicate the importance of magnesium in nut production. Within two weeks after treatments were started, symptoms of calcium deficiency became apparent by restricted growth and the appearance of small interveinal brown pitted areas accompanied by marginal chlorosis on the upper surface of fully developed leaflets proximal to the growing tips.…”
Section: Methodsmentioning
confidence: 79%
See 2 more Smart Citations
“…Magnesium deficiency as previously reported by BLEDSOE, et al, (2) (19) indicate the importance of magnesium in nut production. Within two weeks after treatments were started, symptoms of calcium deficiency became apparent by restricted growth and the appearance of small interveinal brown pitted areas accompanied by marginal chlorosis on the upper surface of fully developed leaflets proximal to the growing tips.…”
Section: Methodsmentioning
confidence: 79%
“…The middle leaves of lateral branches and the following stages of fruit development were selected from each plant for mineral analysis: (1) gynophores prior to entering the sanid of the fruiting medium, (2) The necessity of aii externial suiplyp of nuiitrienits in both the rooting and fruiting media of the peanuit plant for optimum growth and fruit production is shown in tables 1, II, and IIT. Without exception it was found that plants supplied with the complete solution in the rooting medium, irrespective of the nature of the fruiting medium, notably surpassed the plants of all other cultures not only in the total amount of vegetative growth, flower and gynophore production, but also in the character of growth and general appearance of the plants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bledsoe et al (3) reported a relationship between the magnesium content of leaf tissue and the incidence of peanut leafspot. They found that plants grown at low magnesium levels had less magnesium in the leaf tissue and developed about fifty times more leaf spots than did plants grown at high magnesium levels.…”
mentioning
confidence: 99%
“…The influence of nutrition on the severity of plant diseases has received considerable attention (3,7,15,16,17,18,20,21,22,23). Wingard (25) gives a general review of the literature pertaining to this subject.…”
mentioning
confidence: 99%